Bioorthogonal microglia-inspired mesenchymal stem cell bioengineering system creates livable niches for enhancing ischemic stroke recovery via the hormesis - Jianpei Xu; Yinzhe Sun; Yang You; Yuwen Zhang; Dan Huang; Songlei Zhou; Yipu Liu; Shiqiang Tong; Fenfen Ma; Qingxiang Song; Chengxiang Dai; Suke Li; et al. (Acta Pharmaceutica Sinica B, 2024)
Mesenchymal stem cells (MSCs) experience substantial viability issues in the stroke infarct region, limiting their therapeutic efficacy and clinical translation. High levels of deadly reactive oxygen radicals (ROS) and proinflammatory cytokines (PC) in the infarct milieu kill transplanted MSCs, whereas low levels of beneficial ROS and PC stimulate and improve engrafted MSCs' viability. Based on the intrinsic hormesis effects in cellular biology, we built a microglia-inspired MSC bioengineering system to transform detrimental high-level ROS and PC into vitality enhancers for strengthening MSC therapy. This system is achieved by bioorthogonally arming metabolic glycoengineered MSCs with microglial membrane-coated nanoparticles and an antioxidative extracellular protective layer. In this system, extracellular ROS-scavenging and PC-absorbing layers effectively buffer the deleterious effects and establish a micro-livable niche at the level of a single MSC for transplantation. Meanwhile, the infarct's inanimate milieu is transformed at the tissue level into a new living niche to facilitate healing. The engineered MSCs achieved viability five times higher than natural MSCs at seven days after transplantation and exhibited a superior therapeutic effect for stroke recovery up to 28 days. This vitality-augmented system demonstrates the potential to accelerate the clinical translation of MSC treatment and boost stroke recovery.